Perceived Barriers to Exercise in Women with Gestational Diabetes Mellitus - Arasoo, Valliammai Jayanthi Thirunavuk; Dominic, Nisha Angela; Ramadas, Amutha; Lim, Kean Heng; Tionga, Chong Wei; Liew, Ena; Tang, Jing Ling; Jeganathan, Ravichandran (IIUM Medical Journal Malaysia, 2018)
Introduction: Good control of glycaemia negates potential maternal and fetal complications. A diet suitable for women with gestational diabetes mellitus (GDM) is a first line approach. However, little is said about suitable exercise in pregnancy that will potentially help control glycaemia. This pilot study seeks to understand the perceived barriers to exercise in women with GDM. Materials and Methods: This crosssectional study recruited patients with GDM on diet control at the antenatal clinic of Hospital Sultanah Aminah Johor Bahru, Malaysia between October 2017 and January 2018. Those who fulfilled the recruitment criteria were approached and 89 women consented to participate. Data was obtained from antenatal records and a self-administered questionnaire. Results: The mean age of the participants was 33.3 years. More than 80% were Para 1 and above. 69.6% were either overweight or obese at booking of pregnancy. 80.9% were aware that exercise was necessary for women with GDM. Only 6.7% say that healthcare professionals were their source of information on exercise in pregnancy. 77.3% of the women with low physical activity had full time jobs. Housewives (64.5%) had the highest level of physical activity. Tiredness (43.8%), childcare duties (38.2%) and lack of time (27.0%) were the most common perceived barriers to exercise. Nulliparity was significantly associated with tiredness. Conclusion: Main barriers to exercise are tiredness and childcare duties. Health care professionals did little in educating women with GDM on suitable exercise.